Emulsões com colágeno extraído de resíduo do beneficiamento de Tilápia com extrato de Phyllanthus niruri com propriedade antioxidante - Lima, Grazielly Cardoso (2018)
Emulsions are systems composed of two immiscible liquids, thermodynamically unstable and with a particle diameter greater than 200 nm. Due to the pleasant sensory properties, low irritability, optimum moisturizing, spreadability, in addition to rapid penetration of skin images, they have attention of the various areas of study. Therefore, this work presents collagen emulsions extracted from Nile Tilapia (Oreochromis niloticus) processing residues for the incorporation of aqueous extracts of dry leaves the Phyllanthus niruri. Collagen was extracted from the demineralized Tilapia scales by the enzyme method and by the aqueous extract of Phyllanthus niruri, being used as an aqueous extractor of pressurized solvent (ASE). Stable emulsions with the combination of olive oil, sorbitan monooleate and polysorbate 80 by the high energy method using tip ultrasound. The stability was analysed by macroscopic, centrifugation, pH, zeta potential, polydispersity and electrical conductivity. The EHL value required for sunflower oil is studied and recorded equal to 7.0. To determine thebest formulation, a ternary diagram was constructed,noting that the experimente 29 (80% water, 10% surfactant and 10% oil), showed greater stability. Primary testes the emulsion containing collagen (0.1%, 0.25%, 0.5%, 0.75% and 1%) were done. The emulsions containing 0.1% and 0.5% obtained the highest macroscopic stability, even after centrifugation, but the size was 634.6 and 715.1 nm, respectively. Several other emulsions were formulated until arrive an F'1 emulsion, added to the aqueous Phyllanthus extract. In this emulsion, in addition to the stability tests, cytotoxic activity was carried out against tumor lines of the uterine colon, prostate, leukemia and astrocytoma. This in vitro activity studies, showed activity, however, it is necessary to review tests with higher concentrations, aiming to improve their cytotoxic action.